Study of Ammonia-Nitrogen and Phosphorus in Parit Rasipan Canal During the Wet Season - Hamdan, Rafidah; Miswan, Muhammad Safwan; Edros, Nor Wani; Ab Aziz, Nur Adila; Siddiqui, Zuhaib (International Journal of Integrated Engineering, 2023)
The Parit Rasipan Canal’s deteriorating water quality and eutrophication are both blamed on ammonia-nitrogen and phosphorus. In order to conserve freshwater resources, it is crucial to understand the relationship between land use and water quality. It is also crucial to evaluate how land use affects the pollutants load. In this study, eutrophication along the Parit Rasipan drainage system will be identified, water quality will be investigated in terms of phosphorus and ammonia nitrogen concentration and classified according to land use type during the wet season, and ammonia-nitrogen and phosphorus concentrations will be compared with Normalized Difference Vegetation Index (NDVI) using unmanned aerial vehicles (UAV). At a specific location along the Parit Rasipan drainage system, samples were taken. The USEPA PhosVer 3 with Acid Persulfate Digestion Procedure (Method 8190) and Nessler’s Method (Method 8038) were used, respectively, to measure phosphorus and ammonia nitrogen. Ammonia nitrogen and phosphorus final effluent concentrations ranged from 3.21 mg/L to 5.96 mg/L and 0.36 mg/L to 1.55 mg/L, respectively. The residential area’s water, on the other hand, had significant concentrations of ammonia, nitrogen, and phosphorus, which contributed to eutrophication in the wake of industrial, agricultural, and farming activities.